Molecular phylogeny of the grasshopper family Pyrgomorphidae (Caelifera, Orthoptera) reveals rampant paraphyly and convergence of traditionally used taxonomic characters - Zahid, Sundus; Mariño-Pérez, Ricardo; Song, Hojun (Zootaxa, 2021)
The grasshopper family Pyrgomorphidae is one of the most colorful orthopteran lineages, and includes biologically fascinating and culturally important species. Recent attempts to reconstruct the phylogeny of this family have resulted in a large degree of conflicts between a morphology-based study and a molecular-based study, mainly due to convergent morphological traits that affected phylogenetic reconstruction. In this study, a molecular phylogeny of Pyrgomorphidae based on 32 ingroup species and mitochondrial genome data is proposed, which is used to test the monophyly of the taxonomic groupings used in the current classification scheme. Using the ancestral character state reconstruction analyses and character mapping, we demonstrate that some of the morphological characters, including the male genitalia, which were considered to be taxonomically important, have evolved convergently across the phylogeny. We discuss the discrepancies between our phylogeny and the previous studies and propose an approach to establish a natural classification scheme for Pyrgomorphidae.